Bank Competition and Economic Growth: A Cross-Country Investigation - Laowattanabhongsea, Sanhapas; Sukcharoensin, Sorasart (SOUTHEAST ASIAN JOURNAL OF ECONOMICS, 2018)
The relationship between bank competition and economic growth is still a controversial issue. There are two opposing hypotheses: more- competition-less-growth and more-competition-more-growth. This paper, therefore, attempts to conclude the relationship under the competition-growth nexus by using a sample of 81 countries covering both developed and developing countries during the years 2000 to 2013. The empirical results reveal that two main measures for bank competition, specifcally market pricing power and market concentration, indeed have opposite efects on economic growth. In addition, given the same level of competition, the economic growth tends to be higher in countries with lower level of accessibility to bank funding, lower credit to the private sector and a more efcient banking system. These fndings have signifcant policy implications to analyse the efect of competition in the fnancial sector on economic growth.